Efficacy and safety of the recombinant human growth hormone in short children born small for gestational age: A randomized, multicentre, comparative phase III trial. Issue 30 (30th July 2021) - Kim, Su Jin; Kim, Min-Sun; Cho, Sung Yoon; Suh, Byung-Kyu; Ko, Cheol Woo; Lee, Kee-Hyoung; Yoo, Han-Wook; Shin, Choong Ho; Hwang, Jin Soon; Kim, Ho-Seong; Chung, Woo Yeong; Kim, Chan Jong; et al.
Abstract: Objective: Growth hormone (GH) treatment is known to be effective in increasing stature in children with a short stature born small for gestational age (SGA). This multicentre, randomized, open-label, comparative, phase III study aimed to evaluate the efficacy and safety of Growtropin-II (recombinant human GH) and to demonstrate that the growth-promoting effect of Growtropin-II is not inferior to that of Genotropin in children with SGA (NCT ID: NCT02770157). Methods: Seventy five children who met the inclusion criteria were randomized into 3 groups in a ratio of 2:2:1 (the study group [Growtropin-II, n = 30], control group [Genotropin, n = 30], and 26-week non-treatment group [n = 15]). The study and control groups received subcutaneous injections of Growtropin-II and Genotropin, respectively for 52 weeks, whereas the non-treatment group underwent a non-treatment observation period during weeks 0 to 26 and a dosing period during weeks 27 to 52 and additional dosing till week 78 only in re-consenting children. Results: No significant differences in demographic and baseline characteristics between the groups were observed. The mean ± standard deviation change difference in annualized height velocity (aHV) (study group - control group) was 0.65 ±2.12 cm/year (95% confidence interval [CI], −0.53 to 1.83), whereas the lower limit for the 2-sided 95% CI was −0.53 cm/year. Regarding safety, treatment-emergent adverse events (TEAEs) occurred in 53.33% children in the study group and 43.33% children in the control group; the difference in the incidence of TEAEs between the 2 treatment groups was not statistically significant ( P = .4383). A total of 17 serious adverse events (SAEs) occurred in 13.33% children in the treatment groups, and no significant difference in incidence between groups ( P = .7065) was seen. Two cases of adverse drug reaction (ADR) occurred in 2 children (3.33%): 1 ADR (injection site swelling or pain) occurred in 1 child (3.33%) each in the study and control groups. Conclusions: This study demonstrates that the change in aHV from the baseline till 52 weeks with Growtropin-II treatment is non-inferior to that with Genotropin treatment in children with short stature born SGA. Growtropin-II is well-tolerated, and its safety profile is comparable with that of Genotropin over a 1-year course of treatment.